Clinical validation of circulating immune complexes for use as a diagnostic marker of canine leishmaniosis - Sarquis, Juliana; Parody, Nuria; Montoya, Ana; Cacheiro-Llaguno, Cristina; Barrera, Juan Pedro; Checa, Rocío; Daza, María Angeles; Carnés, Jerónimo; Miró, Guadalupe (Frontiers in Veterinary Science, 2024)
Canine leishmaniosis (CanL) is a systemic disease that affects dogs. When multiplication of the parasite cannot be controlled, dogs consistently show high levels of antigen and IgG antibodies, which lead to the formation of circulating immune complexes (CIC). Timely intervention to reduce the parasite load and CIC levels is crucial for preventing irreversible organ damage. However, a diagnostic test to quantify CIC levels is currently lacking. In this real-world study, we aimed to examine the performance of a new ELISA to measure CIC levels in dogs naturally infected with Leishmania infantum. Thirty-four dogs were treated according to their clinical condition and followed for 360 days. Before (day 0) and after treatment (days 30, 90, 180, 270 and 360), all dogs underwent a physical examination, and blood samples were obtained for CBC, biochemical profile, serum protein electrophoresis and IFAT. Serum PEG-precipitated CIC were determined by ELISA. Our results indicate higher CIC levels in dogs in advanced disease stages showing higher antibody titres (p< 0.0001, r= 0.735), anemia (p< 0.0001), dysproteinemia (p< 0.0001), and proteinuria (p= 0.004). Importantly, dogs responding well to treatment exhibited declining CIC levels (p< 0.0001), while in poor responders and those experiencing relapses, CIC were consistently elevated. CIC emerged as a robust discriminator of relapse, with an area under the curve (AUC) of 0.808. The optimal cut-off to accurately identify relapse was an optical density of 1.539. Our findings suggest that declining CIC levels should be expected in dogs showing a favourable treatment response. Conversely, in dogs displaying a poor response and recurrent clinical relapses, CIC levels will be high, emphasizing the need for vigilant monitoring. These findings suggest that CIC could serve as a valuable biomarker for disease progression, treatment efficacy, and relapse detection in CanL. Our study contributes to enhancing diagnostic approaches for CanL and underscores the potential of CIC as a complementary tool in veterinary practice. As we move forward, larger studies will be essential to confirm these findings and establish definitive cut-offs for clinical application.